Influence of the Altered Surface Layer on the Corrosion of AA5083. Issue 6 (1st January 2015) - Seong, Jinwook; Yang, Fan; Scheltens, Frank; Frankel, G. S.; Sridhar, N.
Abstract : The corrosion behavior of sensitized AA5083 in aerated and deaerated 3.5 wt% NaCl solutions has been studied. The results indicated that an altered surface layer (ASL) with a recrystallized microstructure having no β phase at the grain boundaries formed on sensitized AA5083 during polishing. The ASL prevented the exposure of β phase at the surface and its dissolution at the alloy open circuit potential, even though this potential was above the breakdown potential of bulk β phase. Selective dissolution of β phase was observed when a cathodic reaction caused an increase in localized pH near intermetallic particles or after removal of the ASL by etching to expose the grain boundary β phase. The different corrosion behavior of solutionized and sensitized AA5083 was clarified by testing etched samples. Removal of the ASL is therefore necessary to understand the initiation of intergranular corrosion on sensitized AA5083.